Outcomes After Concomitant Hip Arthroscopy and Periacetabular Osteotomy: A Systematic Review. Issue 4 (25th April 2023) - Lee, Michael S.; Fong, Scott; Owens, Jade S.; Mahatme, Ronak J.; Kim, David N.; Gillinov, Stephen M.; Moran, Jay; Simington, Jacquelyn; Islam, Wasif; Abu, Seyi; Jimenez, Andrew E.
Background: Despite several studies' reports on outcomes of concomitant hip arthroscopy and periacetabular osteotomy (PAO), there is a paucity of aggregate data in the literature. Purpose: To evaluate outcomes and survivorship after concomitant hip arthroscopy and PAO. Study Design: Systematic review; Level of evidence, 4. Methods: The PubMed, Cochrane, and Scopus databases were searched in April 2022 using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The following keywords were used: (hip OR femoroacetabular impingement) AND (arthroscopy OR arthroscopic) AND (periacetabular osteotomy or rotational osteotomy) AND (outcomes OR follow-up). Of 270 articles initially identified, 10 studies were ultimately included. The following information was recorded for each study if available: publication information; study design; study period; patient characteristics; follow-up time; indications for hip arthroscopy; patient-reported outcomes (PROs); rates of secondary hip preservation surgeries; and rates of conversion to total hip arthroplasty (THA). Survivorship was defined as nonconversion to THA. Results: The study periods for the 10 included articles ranged from 2001 to 2018. Three studies were level 3 evidence, and 7 studies were level 4 evidence. This review included 553 hips with a mean follow-up of 1 to 12.8 years. All 10 studies listed dysplasia as an indication for surgery. Of 9 studies that reported PRO scores, 7 reported significant improvement after surgery. Studies with a <5-year follow-up reported conversion to THA rates of 0% to 3.4% and overall secondary surgery rates of 0% to 10.3%. Similarly, studies with >5-year follow-up reported conversion to THA rates of 0% to 3% and overall secondary surgery rates of 0% to 10%. Conclusion: Patients who underwent concomitant hip arthroscopy and PAO reported favorable outcomes, with 7 of the 9 studies that provided PRO scores indicating significant preoperative to postoperative improvement.